Skrining SRQ-20 dan Solusi Komunitas Gangguan Mental Emosional Anak Pekerja Migran di Kuala Lumpur - Kaeston Restugusti Genharyo Kamajaya; Ichda Puspita Nagari; Madhura Athallah Nugroho; Tiara Safa Earlene; Wahyu Gito Putro; Arief Tajally Adhiatma; Aisyah Lahdji (TRIAGE Jurnal Ilmu Keperawatan, 2026)
Emotional mental disorders resulting from bullying are an important public health issue among children in non-formal educational settings in Malaysia, particularly those from Indonesian migrant worker families with social vulnerability and limited psychosocial support. This study aimed to analyze emotional mental disorders resulting from bullying using the Self-Reporting Questionnaire-20 (SRQ-20) and to conduct structured problem analysis and solution planning at Sanggar Bimbingan Kampung Bharu, Kuala Lumpur. A descriptive-analytic cross-sectional design was applied with total sampling of 37 students. Data normality was assessed using the Shapiro–Wilk test. Associations between age and total SRQ-20 score were analyzed using Spearman rank correlation, while associations between gender and emotional mental disorder categories and individual SRQ-20 items were examined using Chi-square and Fisher Exact tests. Problem analysis included identification, prioritization, solution formulation, and cost–benefit–based decision-making. The results showed that 67.6% of respondents had indications of emotional mental disorders, with persistent fatigue as the most dominant symptom (72.0%), followed by anxiety-related symptoms (64.0%) and feelings of unhappiness (56.0%). Age was significantly correlated with total SRQ-20 score (r = −0.354; p = 0.032). No significant association was found between gender and overall emotional mental disorder category (p = 0.909); however, gender was significantly associated with persistent fatigue (p = 0.027). Based on problem analysis, a Plan of Action (PoA) focusing on mental health education, early detection, and bullying prevention was developed. In conclusion, integrated analysis and intervention improved students’ understanding of bullying, its mental health impacts, and appropriate preventive actions.